Importancia de los elementos de protección personal (EPP) en la Industrias Metalmecánica En Colombia. (2015)
This article aims to demonstrate the importance of the protection elements staff (EPP) in the metalworking industry, which are described in detail taking into account the risk factors that impact most often in the metalworking activities such as physical hazards (noise and welding), mechanical hazards and finally working at height. Considering the above, as a measure for risk reduction referred to in the implementation of a safety management system and occupational health described in NTC-OHSAS 18001: 2007. The methodology used in this research is analytical and descriptive, based on the collection of information and data from secondary sources that make it possible inference of PPE in the metalworking sector describing its use, prevention and guarantees given to employees against the imminent risks labor in order to counteract them.